2020
DOI: 10.3168/jds.2020-18643
|View full text |Cite
|
Sign up to set email alerts
|

The association of cow-related factors assessed at metritis diagnosis with metritis cure risk, reproductive performance, milk yield, and culling for untreated and ceftiofur-treated dairy cows

Abstract: Our objective was to assess the association of cowrelated factors with metritis cure risk and economically important outcomes. In this prospective cohort study nested inside a randomized clinical trial, cows enrolled in a clinical trial that aimed to evaluate an alternative metritis therapy that had available plasma samples collected at metritis diagnosis were included. Metritis was defined as fetid, watery, reddish-brownish discharge with or without fever, and cure was defined as the absence of metritis signs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 46 publications
1
14
0
Order By: Relevance
“…It is unclear why these variables were not associated with cure by traditional logistic regression. Machado et al (2020) found no association between parity and cure of metritis at 12 d after metritis diagnosis, consistent with our findings. Also, Lima et al (2014) observed that parity was not associated with cure up to 12 d after enrollment.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…It is unclear why these variables were not associated with cure by traditional logistic regression. Machado et al (2020) found no association between parity and cure of metritis at 12 d after metritis diagnosis, consistent with our findings. Also, Lima et al (2014) observed that parity was not associated with cure up to 12 d after enrollment.…”
Section: Discussionsupporting
confidence: 91%
“…Studies using machine learning have been used to predict cow performance or disease events using large and complex data sets (Shahinfar et al, 2012;Hempstalk et al, 2015). Studies indicate that risk factors for metritis and environmental fac-tors could increase the chance of treatment failure (de Oliveira et al, 2020;Machado et al, 2020). However, there is limited information showing whether or not factors influencing metritis cure in treated and nontreated cows are similar.…”
Section: Introductionmentioning
confidence: 99%
“…These include metritis, RFM, ketosis, low BCS, and endometritis, which are associated with negative effects on reproductive performance. Prolonged interval from calving to pregnancy has been reported to be associated with metritis (Barański et al, 2012;Giuliodori et al, 2013;Machado et al, 2020), RFM (Martin et al, 1986), ketosis (Rutherford et al, 2016), andlow BCS at 40-60 DIM (van Straten et al, 2009). Ketosis, RFM, and low BCS were also associated with a prolonged interval from calving to first insemination (Martin et al, 1986;van Straten et al, 2009;Rutherford et al, 2016); and ketosis was reported to be associated with lower first AI conception rate as well (Rutherford et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…However, there is limited evidence of the benefit of antimicrobial therapy for PM cases aside from improvement of fever (McLaughlin et al, 2012). A 21.8% spontaneous cure rate has been reported when antimicrobial therapy was delayed until the fifth day postpartum when cows were followed during the first 10 DIM, which could imply a reduction in antimicrobial use in cows with PM that recovered within the first 5 d (Sannmann et al, 2013) or, spontaneous cure 12 d after diagnosis in 64.6% of untreated cows with PM (Machado et al, 2020). Aside from this, there are rising concerns with antimicrobial resistance and pressure toward improving antimicrobial drug stewardship on dairy farms (Tragesser et al, 2006;Taylor et al, 2019).…”
Section: Discussionmentioning
confidence: 99%